1,3,5,7-Tetrathia-s-indacene-2,6-dithione as Potential Building Block for « Polyfulvalenes» - Peter Wolf; Klaus Müllen; Michael Przybylski (CHIMIA)
The synthesis of the hitherto unknown title compound [also called «1,2:4,5- benzobis(1,3-dithiole-2-thione)»] (3a) and its «3,6»-diiosopropyl derivative 3b is reported. The dithione 3a can be doubly protonated to yield a dication. 3a is a potential precursor of poly-conjugated organic conductors of the tetrathiafulvalene series. 3a is self-coupled with the aid of triethylphosphite to yield the fulvalene 4 (n = 0), which is identified by its FAB-MS- and Raman spectra.